Neoplasia mamária em cadelas: aspectos clínico-cirúrgicos - Gomide, Paula Regina Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Oncology is presenting an important role in clinical practice as a speciality in recent years in Veterinary Medicine. Mammary gland tumors are detected mainly in old and middleaged bitches that are sexually intact or spayed and the caudal abdominal and inguinal mammary glands are the most affected and they present a percentage up to 75% of malignancy. The majority of dogs with mammary neoplasms are clinically healthy at the time of diagnosis and the tumors can be identified by the owner or a professional during a routine physical examination. Cytological examination of fine needle aspirates can be performed. This procedure is easy and low cost and some criteria that may indicate malignancy are evaluated, however to obtain a definitive diagnosis is performed histopathology of the excised tissue or from biopsy. Regional lymph nodes are the first lymph node to receive lymphatic drainage from the neoplasm. They are at the highest risk of regional metastasis, while the lung is the most common site for distant metastasis. Determining the clinical stage enables the definition of the extension of the tumor. As a consequence, this allows a prognosis to be established and treatment to be planned. The type of therapy to be chosen incites controversy since there are numerous treatment options described, but the surgery is the chosen treatment. However, surgery is not always effective for malignant tumors, and recurrences may occur and in these cases, auxiliary chemotherapy treatments are used. The prognosis for animals that have mammary tumors depends on several factors, such as: size, stage, type of tumor cells and clinical behavior of the tumor, age and medical condition of the animal, and presence of metastasis. Because of this, more detailed studies are needed based on epidemiological surveys in order to provide more informations about risk factors, prevalence and follow-up after treatment of mammary... (Complete abstract click electronic access below)

A oncologia vem apresentando papel de destaque como especialidade na rotina clínica nos últimos anos em Medicina Veterinária. Os tumores das glândulas mamárias são detectados principalmente em cadelas velhas e de meia idade, sejam elas inteiras ou castradas, e os pares de mamas abdominal caudal e inguinal são os mais acometidos apresentando uma porcentagem de até 75% de malignidade. A maioria dos animais com neoplasia mamária é clinicamente saudável no momento do diagnóstico e os tumores podem ser identificados pelos proprietários ou pelo profissional. O exame citológico pode ser realizado, pois é um procedimento fácil e de baixo custo e alguns critérios que podem indicar malignidade são avaliados, porém para se obter o diagnóstico definitivo, é realizada a histopatologia do tecido excisado ou proveniente de biópsia. Os linfonodos regionais são os primeiros a receber a drenagem linfática do tumor. Eles fazem parte do maior risco de metástase regional, enquanto que o pulmão é o mais acometido pela mestástase à distância. Determinar o estágio clínico do tumor mamário permite a definição da extensão do tumor. Como conseqüência, isso permite estabelecer um prognóstico e planejar o tratamento. O tipo de terapia a ser escolhida gera controvérsias visto que há inúmeras opções terapêuticas descritas, mas a intervenção cirúrgica é o tratamento de escolha. Entretanto, nem sempre a remoção cirúrgica é eficaz para tumores malignos, podendo ocorrer recidivas e, para isso, são usados tratamentos auxiliares. O prognóstico dos animais que apresentam neoplasias mamárias depende de diversos fatores, dos quais se destacam: estadiamento, tipo de células neoplásicas e comportamento clínico do tumor, idade e condição clínica do animal, e presença de metástases. Em razão disto, observase uma necessidade grande de estudos mais minuciosos com a finalidade... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Cão; Mamas - Cancer; Mastectomia